A highly selective and sensitive fluorescence probe based on Rhodol for imaging of endogenous peroxynitrite in living cells. (October 2022) - Wu, Jiancheng; Lin, Yanfei; Yu, Yating; Li, Yanbo; Ye, Tianqing; Zhou, Hongwei; Li, Lei; Wang, Jianbo
Abstract: Peroxynitrite (ONOO − ), as one of the important reactive oxygen/nitrogen species, is associated with many physiological and pathological activities. Therefore, effective detection methods with high sensitivity and rapid response time are essential to reveal its functions. A novel Rhodol-based fluorescent probe RN is constructed and synthesized by introducing of 1, 1-dimethylhydrazone as a recognition group. Due to the oxidative breakage of the CN bond by ONOO −, the probe has significant fluorescence enhancement change with excellent detection properties such as rapid response time, high sensitivity and selectivity. Moreover, probe RN show low cytotoxicity and is successfully capable of imaging endogenous and endogenous ONOO − in living cells. These properties indicate that RN has great application potential for imaging of ONOO − in biological systems. Graphical abstract: Image 1 Highlights: New Rhodol derivative is designed as fluorescent probe (RN ) for monitoring of ONOO − . Probe RN exhibits turn-on fluorescent change toward ONOO − with high sensitivity and rapid response time (<60s). Probe RN can be used for monitoring endogenous ONOO − changes in cells.